Serangga Predator pada Tanaman Kopi Tim-Tim di Desa Rusip Antara Kabupaten Aceh Tengah - Muhammad Fikri Al Munawar; Saniar Fauza; Diah Fridayati (Pangale Journal of Forestry and Environment, 2026)
Coffee (Coffea spp.) is a major agricultural commodity in Indonesia, particularly the Tim-Tim variety cultivated in the highlands of Aceh Tengah. Pest attacks pose a significant threat to coffee production, making the presence of natural enemies essential. This study aimed to identify predatory insects in Tim-Tim coffee plantations in Rusip Antara Village, Aceh Tengah Regency. Sampling was conducted using three trap types: light traps, yellow pan traps, and malaise traps, with three replications over three months. A total of 154 individuals belonging to 11 families were collected. The Shannon-Wiener diversity index (H’) ranged from 3.27 to 3.36, indicating high diversity across all trap types. The evenness index was very high (E = 0.97–1.00), showing no dominant family. Mantidae and Carabidae were the most abundant families. These findings suggest that Tim-Tim coffee agroecosystems in Rusip Antara support high natural biological control potential, reinforced by semi-organic management and shade-grown practices.